Metabolic controls on the carbon isotope fractionations of bacterial fermentation - Elliott P. Mueller; Verena B. Heuer; Jared R. Leadbetter; Kai-Uwe Hinrichs; Alex L. Sessions (Proceedings of the National Academy of Sciences, 2025)
Microbial fermentation facilitates the initial breakdown of organic matter into small molecules and is thought to be the rate-limiting step of anoxic organic mineralization. However, fermentation is understudied in modern and ancient biogeochemistry due to a lack of environmental biomarkers. It has long been assumed that fermentation, like respiration, does not express significant carbon isotope fractionations, precluding isotopic signals as a means of studying it in nature. Here, we tested this idea by growing pure cultures of four fermenting bacteria on glucose and measuring the carbon isotope compositions of the organic acids and alcohols produced. We found that fermentation exhibits a strong carbon isotope fractionation, ranging from − 6‰ to + 16‰, depending on the fermentation product. With bioisotopic models that track site-specific isotope enrichments through metabolism, we constrained the enzymes responsible for these fractionations. Our models reproduced in vivo organic acid δ 13 C values in all four organisms. These findings demonstrate that acetate 13 C-enrichment is likely a widespread signature of fermentation. They also challenge traditional notions of controls on the isotope composition of lipids. Finally, our study suggests that fermentation imposes a trophic carbon isotope fractionation as organic carbon is passed from fermenters to secondary degraders like sulfate reducers. Looking to the geologic past, this trophic fractionation could have imprinted isotopic signals on the three billion year record of sedimentary organic carbon, specifically the inverse δ 13 C pattern of Precambrian acyclic isoprenoid and n-alkane biomarkers. Pervasive evidence of fermentation in the rock record would suggest its underappreciated role in biogeochemical cycles throughout Earth history.